UCZENIE SIĘ PRZEZ DOŚWIADCZENIE, CZYLI METODA PROJEKTÓW W KSZTAŁCENIU ANIMATORÓW KULTURY - Słowińska, Sylwia (Adult Education Discourses, 2010)
The paper aims to present the use of the project method in the training of cultural facilitators at the University of Zielona Góra. As far as preparing for the profession is concerned, the author underlines the importance of students’ practical experiences in the field of cultural work. Cultural facilitating study programs should include both theoretical and practical courses, as well as provide the opportunity to learn by doing. Therefore, the use of the project method is recommended as it consists in solving practical problems and applying the knowledge that students gain during the courses. The authoress presents an example of using this method and – referring to Knud Illeris’s views about experiential learning – describes the concept of a bachelor’s seminar in cultural facilitation based on the project work. The goal of this seminar is to give students the opportunity to execute their own culture facilitation projects and to learn by doing. Afterwards, they should describe and analyse this process in their diploma papers. The author concludes by describing some difficulties that arose during the seminar when using the method in question.